2003
DOI: 10.1023/b:phot.0000027527.08220.2c
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Between Nitrogen Supply and Photosynthetic Parameters in Vicia faba L.

Abstract: We determined for Vicia faba L the influence of nitrogen uptake and accumulation on the values of photon saturated net photosynthetic rate (P Nmax ), quantum yield efficiency (α), intercellular CO 2 concentration (C i ), and carboxylation efficiency (C e ). As leaf nitrogen content (N L ) increased, the α converged onto a maximum asymptotic value of 0.0664±0.0049 µmol(CO 2 ) µmol(quantum) -1 . Also, as N L increased the C i value fell to an asymptotic minimum of 115.80±1.59 µmol mol -1 , and C e converged onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 26 publications
2
6
0
1
Order By: Relevance
“…Theoretically, P max , which determines the plant potential photosynthetic capacity, is proportional to the number of active catalytic sites in chloroplasts that are involved in the reductive assimilation of CO 2 (Jia and Gray 2003). In our study, decreased P max under water stress and increased P max at N supply were respectively associated with stomatal closure and improvement of carboxylation efficiency as discussed above, suggesting that N supply could enhance potential photosynthetic capacity under water deficit.…”
Section: Discussionsupporting
confidence: 67%
“…Theoretically, P max , which determines the plant potential photosynthetic capacity, is proportional to the number of active catalytic sites in chloroplasts that are involved in the reductive assimilation of CO 2 (Jia and Gray 2003). In our study, decreased P max under water stress and increased P max at N supply were respectively associated with stomatal closure and improvement of carboxylation efficiency as discussed above, suggesting that N supply could enhance potential photosynthetic capacity under water deficit.…”
Section: Discussionsupporting
confidence: 67%
“…Aquadulce Claudia (Straathof Seed Group) requiring approximately 130-150 d for crop development was used. Outdoor experimental pot trials were carried out as reported in Jia and Gray (2003). Faba bean seeds were planted in 15 cm diameter (area equivalent to ---0.0177 m 2 ) pots.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that the decreased photosynthesis under salt stress was associated with decreased diffusion of CO 2 to chloroplasts, caused by stomata closure and/or by changes in mesophyll structure (Delfine et al 1998;Netondo et al 2004). On other hand, some works showed that the non-stomatal photosynthesis limitation could be attributed to the perturbations of biochemical processes, such as decrease in ribulose bisphosphate carboxylase/oxygenase (Rubisco) activity, decrease in ribulose-1,5-bisphosphate (Delfine et al 1998), and to the reduced carboxylation efficiency (Jea and Gray 2004). The effect of salt stress on photosynthesis is still controversial.…”
Section: Introductionmentioning
confidence: 99%